High-entropy alloy type FeS2 / C composite material and preparation method and application thereof
By introducing high-entropy alloys and carbon materials into FeS2 materials, the problem of using toxic reaction sources and low conductivity in FeS2 materials during synthesis is solved, and high stability and excellent cycling performance are achieved, which is suitable for battery positive electrode materials.
Patent Information
- Application Number
- CN202411276869.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2045-01-17
AI Technical Summary
The existing FeS2 materials use toxic reaction sources and organic solvents during the synthesis process, and have low conductivity, volume changes during the cycle, resulting in structural damage, and poor stability and rate performance.
Using the preparation method of high-entropy alloy FeS2/C composite material, a composite material with soluble iron source, metal soluble salt and sublimated sulfur are added to the carbon material dispersion, and the hydrothermal reaction is carried out after adding ethylene glycol solution. The carbon material is loaded on FeS2 to form a composite material with an entropy value ≥1R.
The preparation of high-entropy alloy FeS2/C composite materials without pollution, high yield and low energy consumption has been achieved, and the structural stability and cyclic performance of the material have been improved, and the ratio capacity and capacity retention rate have been significantly improved.
Smart Images

Figure CN119542372A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of high entropy alloy material preparation, and in particular to a high entropy alloy type FeS2 / C composite material and a preparation method and application thereof. Background Art
[0002] Electrochemical energy storage and conversion batteries have become one of the most important devices in people's daily lives. As a clean energy technology, rechargeable battery systems are gradually replacing traditional fossil fuels in the energy market and have gained a place in fixed and mobile energy storage products. Among these alternative energy technologies, metal ion batteries are widely used due to their high energy density and long service life. With the continuous development of technology, long life and high safety have become increasingly important in battery design. Metal-polysulfide batteries, as a conversion reaction system with high theoretical energy density and low cost, have attracted widespread attention.
[0003] Pyrite (FeS2) has a high theoretical specific capacity (890mA hg -1 ), stable structure, safe and pollution-free, etc., and is considered to be a cathode material with application prospects. So far, there are many methods for synthesizing FeS2, including sol-gel method, solvothermal method, microwave radiation and solid phase reaction. These methods usually involve toxic reaction sources or organic solvents, and the FeS2 product usually carries a capping agent on its surface, which affects the ion transport and cation exchange process. In addition, the intrinsic conductivity of FeS2 material is low, and the volume shrinks / expands during the cycle, causing the structure of the material to be severely damaged, resulting in poor stability and rate performance during the cycle, which hinders its practical application. In order to improve and enhance the cycle performance of FeS2, researchers have modified FeS2 cathode materials using methods such as morphology design, voltage control, and electrolyte optimization. However, from the perspective of material design, the above scheme does not essentially improve the stability of the material bulk phase. To this end, the present invention provides a high entropy alloy type FeS2 / C composite material and its preparation method and application. Summary of the invention
[0004] The present invention provides a high-entropy alloy type FeS2 / C composite material and a preparation method and application thereof. On the one hand, it avoids the problem that the existing synthetic FeS2 material uses toxic reaction sources and organic reagents, and the prepared product has a capping reagent on the surface, thereby affecting the ion transport and cation exchange process. On the other hand, it solves the technical problems that the existing FeS2 material as a positive electrode material has low conductivity, volume shrinkage / expansion during the cycle process causes serious damage to the structure of the material, resulting in poor stability and rate performance during the cycle. At the same time, a preparation method of a high-entropy alloy type FeS2 / C composite material is provided, which is pollution-free, has high yield and low energy consumption.
[0005] The first object of the present invention is to provide a method for preparing a high entropy alloy type FeS2 / C composite material, comprising the following steps:
[0006] A soluble iron source, three or four metal soluble salts, and sublimated sulfur are added to a carbon material dispersion, and then an ethylene glycol solution is added, stirred to dissolve, and a hydrothermal reaction is carried out at 180-200°C to load the carbon material on FeS2, and a composite material with an entropy value ≥ 1R is obtained, thereby obtaining a FeS2 precursor, centrifuging, washing, obtaining a FeS2 crude product, drying, and grinding to obtain a high entropy alloy type FeS2 / C composite material.
[0007] As a preferred embodiment, the molar ratio of the soluble iron source, the three or four metal soluble salts and the sublimated sulfur is 1:0.17 to 4:5.
[0008] As a preferred embodiment, based on the mass of the high entropy alloy FeS2 / C composite material, the mass of the carbon material accounts for 10% to 20%.
[0009] As a preferred embodiment, the carbon material dispersion is a dispersion of carbon material in N,N-dimethylformamide, and the volume ratio of N,N-dimethylformamide to ethylene glycol solution is 1:1-3.
[0010] As a preferred embodiment, the hydrothermal reaction time is 12 to 24 hours.
[0011] As a preferred embodiment, the three or four metal soluble salts are selected from three or four of cobalt salts, copper salts, manganese salts, nickel salts, zinc salts, molybdenum salts, tin salts, and niobium salts; the metal soluble salts can be selected from CoSO4·7H2O, CuSO4·5H2O, MnSO4·H2O, NiSO4·6H2O, ZnSO4·7H2O, CoCl2·6H2O, CuCl2·2H2O, NiCl2·6H2O, (NH4)2MoO4, SnCl2, MnCl2·4H2O, C 10 H5B 20 .
[0012] As a preferred embodiment, the carbon material is carbon nanotubes, biomatrix carbon, graphene oxide or N, S dual-doped carbon.
[0013] As a preferred embodiment, the iron source is FeCl2·4H2O, Fe(NO3)3, Fe(OH)(CH3COO)2 or FeSO4.
[0014] The second object of the present invention is to provide a high entropy alloy type FeS2 / C composite material prepared by the above preparation method.
[0015] The third object of the present invention is to provide an application of the above-mentioned high entropy alloy FeS2 / C composite material in the preparation of positive electrode sheet materials, specifically, the high entropy alloy FeS2 / C composite material is mixed with acetylene black and binder PVDF in a mass ratio of 8:1:1 and ground for 10 minutes, 0.5 mL of nitrogen-methylpyrrolidone is added dropwise to obtain a slurry, the slurry is coated on a 15 μm copper foil, and dried at 60°C for 12 hours to obtain an entropy alloy FeS2 / C positive electrode sheet.
[0016] Compared with the prior art, the present invention has the following beneficial effects:
[0017] (1) The present invention provides a high entropy alloy type FeS2 / C composite material and its preparation method and application, using iron source, metal soluble salt, sublimed sulfur and carbon material dispersion as raw materials, adding ethylene glycol solution, stirring until dissolved, performing hydrothermal reaction at 180-200°C to obtain FeS2 precursor, centrifuging, washing, obtaining FeS2 crude product, drying, grinding, and obtaining high entropy alloy type FeS2 / C composite material. The high entropy alloy type FeS2 / C composite material is prepared by the solvent thermal reaction of the present invention, which ensures the uniformity of the system during the reaction process, and the synthesized FeS2 / C material has uniform particle size, small particle size and good dispersibility. The present invention greatly improves the utilization rate of reactants, shortens the reaction time, improves the yield, and has the advantages of simple operation, low requirements for reaction equipment, mild conditions, and mass production. A high entropy alloy type FeS2@C composite material with excellent performance is prepared by a simple and efficient preparation method.
[0018] (2) The present invention uses an iron source, a metal soluble salt, sublimated sulfur and a carbon material as synthetic raw materials to prepare a highly disordered high entropy alloy solid solution. By increasing the mixing entropy of the constituent elements, the mixing entropy is maximized as much as possible, thereby stabilizing the FeS2 electrode structure, inhibiting the volume expansion of the FeS2 electrode material and improving its cycle performance. 0.2 Co 0.2 Cu 0.2 Ni 0.2 Mo 0.2 S2 / C composite material, whose entropy value can reach 1.6094R. The rich and flexible component design of high entropy alloy materials can reduce the dependence on a single element, and can regulate the electronic structure of entropy alloy FeS2 electrode materials, especially the Fermi level related to the electrode potential. The multi-element synergy and inherent complex surface of high entropy alloys can provide nearly continuous adsorption energy, which is very suitable for the sulfide FeS2@C electrode reaction system with multi-step cascade reactions. The highly disordered and distorted lattice of high entropy alloys can produce a large number of defects in FeS2 electrode materials, which is conducive to the migration of electrons and ions.
[0019] (3) The high entropy alloy FeS2@C composite material prepared by the present invention is made into a positive electrode material at 5A g -1 At the rate current, the rate capacity is 588.4mA hg -1 , at 0.5A g -1 After 500 charge and discharge cycles at the current density, the discharge capacity remains at 576.8 mA h g -1 , the capacity retention rate is 81.7%.
[0020] (7) The preparation method of the high entropy alloy type FeS2@C composite material provided by the present invention is simple in process, environmentally friendly, high in yield, low in energy consumption, and has a wide range of applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The Fe prepared in Example 2 of the present invention 0.8 Co 0.05 Cu 0.05 Ni 0.05 Mo 0.05 XRD pattern of S2 / C;
[0022] Figure 2 The Fe prepared in Example 2 of the present invention 0.8 Co 0.05 Cu 0.05 Ni 0.05 Mo 0.05 Elemental distribution diagram of S2 / C;
[0023] Figure 3 The Fe prepared in Example 2 of the present invention 0.8 Co 0.05 Cu 0.05 Ni 0.05 Mo 0.05 Transmission electron microscopy image of S2 / C;
[0024] Figure 4 The Fe prepared in Example 2 of the present invention 0.8 Co 0.05 Cu 0.05 Ni 0.05 Mo 0.05 S2 / C rate performance diagram;
[0025] Figure 5 The Fe prepared in Example 2 of the present invention 0.8 Co 0.05 Cu 0.05 Ni 0.05 Mo 0.05 S2 / C at 500mA g -1 Schematic diagram of charge and discharge cycles at different current densities. DETAILED DESCRIPTION
[0026] In order to enable those skilled in the art to better understand the technical solution of the present invention and implement it, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention. The following test methods and detection methods, unless otherwise specified, are conventional methods; the reagents and raw materials, unless otherwise specified, are commercially available.
[0027] Based on the following three technical problems about FeS2 materials proposed in the background technology of the present invention: First, the existing sol-gel method, solvothermal method, microwave radiation and solid phase reaction for synthesizing FeS2 involve toxic reaction sources or organic solvents, and the FeS2 product usually carries a capping agent on its surface, which affects the ion transport and cation exchange process. Second, the intrinsic conductivity of FeS2 material is low, and the volume shrinks / expands during the cycle, causing the structure of the material to be severely damaged, resulting in poor stability and rate performance during the cycle, hindering its practical application. Third, the modification of FeS2 positive electrode materials using methods such as morphology design, voltage control, and electrolyte optimization cannot essentially improve the stability of the material phase.
[0028] In order to solve the above technical problems, the present invention adds an iron source, a metal soluble salt and sublimated sulfur to a dispersion of a carbon material (carbon nanotubes, biomatrix carbon, graphene oxide or N, S dual-doped carbon), then adds an ethylene glycol solution, stirs until dissolved, and performs a hydrothermal reaction at 180-200°C for 12-24 hours to obtain a FeS2 precursor, centrifuges and washes to obtain a crude FeS2 product, which is then dried and ground to obtain a high entropy alloy type FeS2 / C composite material.
[0029] The structural stability and phase stability of a material depend on entropy (△S) and enthalpy (△H), according to the Gibbs free energy (△G) formula, as shown in formula (1):
[0030] ΔG mix =ΔH mix -TΔS mix (1)
[0031] Where △S is the total entropy change, including configurational and kinetic contributions. The Gibbs free energy of a stable system is always the lowest. According to formula (1), it can be inferred that increasing the configurational entropy can increase the total entropy and entropy value, thereby obtaining a lower Gibbs free energy, which is beneficial to improving the structural stability of the material. Therefore, structural stability can be adjusted by manipulating the configurational entropy of the material. This entropy-mediated structural stability opens up a new type of high-performance electrode material with modified and optimized structure.
[0032] Generally, entropy-modified materials are divided into low entropy (S≤0.69R), medium entropy (S=0.69R~1R) and high entropy (S≥1R). R is the gas constant, 8.314J / (mol·K). Configuration entropy (ΔSconfig) is calculated by formula (2):
[0033]
[0034] It should be noted that the molar ratio of the iron source, the metal soluble salt and the sublimated sulfur is 1:0.17 to 4:5. The above-mentioned iron source is FeCl2·4H2O, Fe(NO3)3, Fe(OH)(CH3COO)2 or FeSO4. When the increase or decrease of its dosage is not within the above-mentioned given molar ratio range, the synthesized FeS2 / C composite material cannot reach the expected design entropy value, and the molar ratio between the metal soluble salt and the sublimated sulfur cannot reach 1:2. When the amount of sublimated sulfur increases beyond the given molar ratio, unreacted sulfur impurities are introduced into the target product of the system. When the amount of sublimated sulfur is lower than the given molar ratio, by-products will be introduced into the final product.
[0035] In order to ensure the electrochemical performance of the composite material and thus improve the battery performance, the mass of the carbon material accounts for 10% to 20% of the mass of the high entropy alloy FeS2 / C composite material. When the carbon content is lower than 10%, the electrochemical performance does not improve qualitatively after the FeS2 and C material are composited. When the carbon content is higher than 20%, the system introduces too much carbon material, causing the energy density of the positive electrode material to drop seriously when it is used in the battery.
[0036] In order to further ensure the electrochemical performance of the composite material, the carbon material dispersion is a dispersion of carbon material in N,N-dimethylformamide, and the volume ratio of N,N-dimethylformamide to ethylene glycol solution is 1:1 to 3. The boiling points of N,N-dimethylformamide and ethylene glycol are 152.8°C and 197.3°C, respectively. The mixture of the two can ensure the safety of the hydrothermal reaction in the range of 180 to 200°C. Secondly, the electrochemical performance test shows that the performance is best when the volume ratio of the two falls in this range.
[0037] According to the high entropy design rule, in order to make the composite material reach the expected design entropy value, the three or four metal soluble salts are selected from three or four of cobalt salts, copper salts, manganese salts, nickel salts, zinc salts, molybdenum salts, tin salts, and niobium salts; the metal soluble salts can be selected from CoSO4·7H2O, CuSO4·5H2O, MnSO4·H2O, NiSO4·6H2O, ZnSO4·7H2O, CoCl2·6H2O, CuCl2·2H2O, NiCl2·6H2O, (NH4)2MoO4, SnCl2, MnCl2·4H2O, C 10 H5B 20 .
[0038] The effects are described below through specific embodiments and comparative examples.
[0039] Example 1 (Fe 0.85 Co 0.05 Cu 0.05 Ni 0.05 S2 / C)
[0040] A high entropy alloy type Fe 0.85 Co 0.05 Cu 0.05 Ni 0.05 The preparation method of the S2 / C composite material comprises the following steps:
[0041] Weigh 0.0965g of N, S dual-doped carbon, put it into a beaker, add 20mL of N, N-dimethylformamide (DMF) and ultrasonicate for 15min to obtain solution A, transfer solution A to the inner tank, then weigh 1.352g of FeCl2·4H2O, 1.090g of sublimated sulfur, 0.112g of CoSO4·7H2O, 0.099g of CuSO4·5H2O and 0.105g of NiSO4·6H2O, mix and put them into the inner tank, finally add 40mL of ethylene glycol and place it on a magnetic stirrer to stir until completely dissolved, stir magnetically at room temperature for 2 hours, then transfer it to a high-pressure reactor, place it in a blast drying oven and react at 180℃ for 12h, open the reactor after cooling to room temperature, and obtain a black precipitate. The obtained precipitate is washed three times with deionized water and anhydrous ethanol respectively, and placed in a blast drying oven at 80℃ until completely dried. The dried sample needs to be further ground to obtain the target product Fe 0.85 Co 0.05 Cu 0.05 Ni 0.05 S2 / C.
[0042] Example 2 (Fe 0.8 Co 0.05 Cu 0.05 Ni 0.05 Mo 0.05 S2 / C)
[0043] A high entropy alloy type Fe 0.8 Co 0.05 Cu 0.05 Ni 0.05 Mo 0.05 The preparation method of the S2 / C composite material comprises the following steps:
[0044] Weigh 0.1007g of carbon nanotubes into a beaker, add 20mL of N,N-dimethylformamide (DMF) and ultrasonicate for 15min to obtain solution A, transfer solution A to the inner tank, then weigh 1.272g of FeCl2·4H2O, 1.026g of sublimated sulfur, 0.112g of CoSO4·7H2O, 0.099g of CuSO4·5H2O, 0.105g of NiSO4·6H2O and 0.078g of (NH4)2MoO4, mix and put into the inner tank, finally add 40mL of ethylene glycol and place on a magnetic stirrer to stir until completely dissolved, stir magnetically at room temperature for 2 hours, transfer to a high-pressure reactor, place in a blast drying oven and react at 180℃ for 12h, open the reactor after cooling to room temperature, and obtain a black precipitate. The obtained precipitate is washed three times with deionized water and anhydrous ethanol respectively, and placed in a blast drying oven at 80℃ to completely dry. The dried sample needs to be further ground to obtain the target product Fe 0.8 Co 0.05 Cu 0.05 Ni 0.05 Mo 0.05 S2 / C.
[0045] Example 3 (Fe 0.8 Sn 0.05 Cu 0.05 Ni 0.05 Mo 0.05 S2 / C)
[0046] A high entropy alloy type Fe 0.8 Sn 0.05 Cu 0.05 Ni 0.05 Mo 0.05 The preparation method of the S2 / C composite material comprises the following steps:
[0047] Weigh 0.1083g of biomatrix carbon into a beaker, add 20mL of N,N-dimethylformamide (DMF) and ultrasonicate for 15min to obtain solution A, transfer solution A to the inner tank, then weigh 1.272g of FeCl2·4H2O, 1.026g of sublimated sulfur, 0.076g of SnCl2, 0.099g of CuSO4·5H2O, 0.105g of NiSO4·6H2O and 0.078g of (NH4)2MoO4, mix and put into the inner tank, finally add 40mL of ethylene glycol and place on a magnetic stirrer to stir until completely dissolved, stir magnetically at room temperature for 2 hours, transfer to a high-pressure reactor, place in a blast drying oven and react at 180℃ for 12h, open the reactor after cooling to room temperature, and obtain a black precipitate. The obtained precipitate is washed three times with deionized water and anhydrous ethanol respectively, and placed in a blast drying oven at 80℃ until completely dry. The dried sample needs to be further ground to obtain the target product Fe0.8 Sn 0.05 Cu 0.05 Ni 0.05 Mo 0.05 S2 / C.
[0048] Example 4 (Fe 0.6 Co 0.1 Cu 0.1 Ni 0.1 Mo 0.1 S2 / C)
[0049] A high entropy alloy type Fe 0.6 Co 0.1 Cu 0.1 Ni 0.1 Mo 0.1 The preparation method of the S2 / C composite material comprises the following steps:
[0050] Weigh 0.1204g of carbon nanotubes into a beaker, add 20mL of N,N-dimethylformamide (DMF) and ultrasonicate for 15min to obtain solution A, transfer solution A to the inner tank, then weigh 0.954g of FeCl2·4H2O, 1.026g of sublimated sulfur, 0.225g of CoSO4·7H2O, 0.200g of CuSO4·5H2O, 0.210g of NiSO4·6H2O and 0.157g of (NH4)2MoO4, mix and put into the inner tank, finally add 40mL of ethylene glycol and place on a magnetic stirrer to stir until completely dissolved, stir magnetically at room temperature for 2 hours, transfer to a high-pressure reactor, place in a blast drying oven and react at 180℃ for 12h, open the reactor after cooling to room temperature, and obtain a black precipitate. The obtained precipitate is washed three times with deionized water and anhydrous ethanol respectively, and placed in a blast drying oven at 80℃ to completely dry. The dried sample needs to be further ground to obtain the target product Fe 0.6 Co 0.1 Cu 0.1 Ni 0.1 Mo 0.1 S2 / C.
[0051] Example 5 (Fe 0.4 Co 0.15 Cu 0.15 Ni 0.15 Mo 0.15 S2 / C)
[0052] A high entropy alloy type Fe 0.4 Co 0.15 Cu 0.15 Ni 0.15 Mo 0.15 The preparation method of the S2 / C composite material comprises the following steps:
[0053] Weigh 0.1551g of N, S dual-doped carbon into a beaker, add 20mL of N, N-dimethylformamide (DMF) and ultrasonicate for 15min to obtain solution A, transfer solution A to the inner tank, then weigh 0.636g of FeCl2·4H2O, 1.026g of sublimated sulfur, 0.337g of CoSO4·7H2O, 0.300g of CuSO4·5H2O, 0.315g of NiSO4·6H2O and 0.235g of (NH4)2MoO4, mix and put into the inner tank, finally add 40mL of ethylene glycol and place on a magnetic stirrer to stir until completely dissolved, stir magnetically at room temperature for 2 hours, then transfer to a high-pressure reactor, place in a blast drying oven and react at 180℃ for 12h, open the reactor after cooling to room temperature, and obtain a black precipitate. The obtained precipitate is washed three times with deionized water and anhydrous ethanol respectively, and placed in a blast drying oven at 80℃ to completely dry. The dried sample needs to be further ground to obtain the target product Fe 0.4 Co 0.15 Cu 0.15 Ni 0.15 Mo 0.15 S2 / C.
[0054] Example 6 (Fe 0.2 Co 0.2 Cu 0.2 Ni 0.2 Mo 0.2 S2 / C)
[0055] A high entropy alloy type Fe 0.2 Co 0.2 Cu 0.2 Ni 0.2 Mo 0.2 The preparation method of the S2 / C composite material comprises the following steps:
[0056] Weigh 0.2048g of biomatrix carbon into a beaker, add 20mL of N,N-dimethylformamide (DMF) and ultrasonicate for 15min to obtain solution A, transfer solution A to the inner tank, then weigh 0.318gCl2·4H2O, 1.026g of sublimated sulfur, 0.450gCoSO4·7H2O, 0.400gCuSO4·5H2O, 0.421gNiSO4·6H2O and 0.314g of (NH4)2MoO4, mix and put into the inner tank, finally add 40mL of ethylene glycol and place on a magnetic stirrer to stir until completely dissolved, stir magnetically at room temperature for 2 hours, transfer to a high-pressure reactor, place in a blast drying oven and react at 180℃ for 12h, open the reactor after cooling to room temperature, and obtain a black precipitate. The obtained precipitate is washed three times with deionized water and anhydrous ethanol, and placed in a blast drying oven at 80℃ to completely dry. The dried sample needs to be further ground to obtain the target product Fe 0.2 Co 0.2 Cu 0.2 Ni 0.2 Mo 0.2 S2 / C.
[0057] Example 7 (Fe 0.52 Co 0.12 Mn 0.12 Mo 0.12 Ni 0.12 S2 / C)
[0058] A high entropy alloy type Fe 0.52 Co 0.12 Mn 0.12 Mo 0.12 Ni 0.12 The preparation method of the S2 / C composite material comprises the following steps:
[0059] Weigh 0.1003g of N, S dual-doped carbon into a beaker, add 20mL of N, N-dimethylformamide (DMF) and ultrasonicate for 15min to obtain solution A, transfer solution A to the inner tank, then weigh 0.827g of FeCl2·4H2O, 1.026g of sublimated sulfur, 0.270g of CoSO4·7H2O, 0.162g of MnSO4·H2O, 0.252g of NiSO4·6H2O and 0.188g of (NH4)2MoO4, mix and put into the inner tank, finally add 40mL of ethylene glycol and place on a magnetic stirrer to stir until completely dissolved, stir magnetically at room temperature for 2 hours, then transfer to a high-pressure reactor, place in a blast drying oven and react at 180℃ for 12h, open the reactor after cooling to room temperature, and obtain a black precipitate. The obtained precipitate is washed three times with deionized water and anhydrous ethanol respectively, and placed in a blast drying oven at 80℃ to completely dry. The dried sample needs to be further ground to obtain the target product Fe 0.5 2Co 0.12 Mn 0.12 Mo 0.12 Ni 0.12 S2 / C.
[0060] Example 8 (Fe 0.52 Co 0.12 Mn 0.12 Mo 0.12 Nb 0.12 S2 / C)
[0061] A high entropy alloy type Fe 0.52 Co 0.12 Mn 0.12 Mo 0.12 Nb 0.12 The preparation method of the S2 / C composite material comprises the following steps:
[0062] Weigh 0.1036 g of carbon nanotubes into a beaker, add 20 mL of N,N-dimethylformamide (DMF) and sonicate for 15 min to obtain solution A. Transfer solution A to the inner tank, then weigh 0.827 g of FeCl2·4H2O, 1.026 g of sublimated sulfur, 0.270 g of CoSO4·7H2O, 0.162 g of MnSO4·H2O, and 0.517 g of C 10 H5B 20Mix with 0.188g (NH4)2MoO4 and put it into the inner container. Finally, add 40mL ethylene glycol and place it on a magnetic stirrer to stir until it is completely dissolved. After magnetic stirring at room temperature for 2 hours, transfer it to a high-pressure reactor and place it in a forced air drying oven to react at 180°C for 12 hours. After the reactor is cooled to room temperature, open it to obtain a black precipitate. Wash the obtained precipitate with deionized water and anhydrous ethanol three times each, and place it in a forced air drying oven at 80°C until it is completely dry. The dried sample needs to be further ground to obtain the target product Fe 0.52 Co 0.12 Mn 0.12 Mo 0.12 Nb 0.12 S2 / C.
[0063] Example 9 (Fe 0.52 Co 0.12 Mn 0.12 Mo 0.12 Sn 0.12 S2 / C)
[0064] A high entropy alloy type Fe 0.52 Co 0.12 Mn 0.12 Mo 0.12 Sn 0.12 The preparation method of the S2 / C composite material comprises the following steps:
[0065] Weigh 0.106 g of N, S dual-doped carbon into a beaker, add 20 mL of N, N-dimethylformamide (DMF) and sonicate for 15 min to obtain solution A, transfer solution A to the inner tank, and then weigh 0.827 g of FeCl2·4H2O, 1.026 g of sublimated sulfur, 0.270 g of CoSO4·7H2O, 0.162 g of MnSO4·H2O, and 0.517 g of C 10 H5B 20 Mix with 0.182g SnCl2 and put it into the inner tank. Finally, add 40mL ethylene glycol and place it on a magnetic stirrer to stir until it is completely dissolved. After magnetic stirring at room temperature for 2 hours, transfer it to a high-pressure reactor and place it in a forced air drying oven to react at 180°C for 12 hours. After the reactor is cooled to room temperature, open it to obtain a black precipitate. Wash the obtained precipitate with deionized water and anhydrous ethanol three times each, and place it in a forced air drying oven at 80°C until it is completely dry. The dried sample needs to be further ground to obtain the target product Fe 0.52 Co 0.12 Mn 0.12 Mo 0.12 Sn 0.12 S2 / C.
[0066] Example 10 (Fe0.52 Co 0.12 Zn 0.12 Mo 0.12 Sn 0.12 S2 / C)
[0067] A high entropy alloy type Fe 0.52 Co 0.12 Zn 0.12 Mo 0.12 Sn 0.12 The preparation method of the S2 / C composite material comprises the following steps:
[0068] Weigh 0.107g of biomatrix carbon into a beaker, add 20mL of N,N-dimethylformamide (DMF) and ultrasonicate for 15min to obtain solution A, transfer solution A to the inner tank, then weigh 0.827g of FeCl2·4H2O, 1.026g of sublimated sulfur, 0.270g of CoSO4·7H2O, 0.276g of ZnSO47H2O, 0.188g of (NH4)2MoO4 and 0.182g of SnCl2, mix and put into the inner tank, finally add 40mL of ethylene glycol and place on a magnetic stirrer to stir until completely dissolved, stir magnetically at room temperature for 2 hours, transfer to a high-pressure reactor, place in a blast drying oven and react at 180℃ for 12h, open the reactor after cooling to room temperature, and obtain a black precipitate. The obtained precipitate is washed three times with deionized water and anhydrous ethanol, and placed in a blast drying oven at 80℃ until completely dry. The dried sample needs to be further ground to obtain the target product Fe 0.52 Co 0.12 Mn 0.12 Mo 0.12 Sn 0.12 S2 / C.
[0069] Example 11 (Fe 0.52 Zn 0.12 Mn 0.12 Mo 0.12 Sn 0.12 S2 / C)
[0070] A high entropy alloy type Fe 0.52 Zn 0.12 Mn 0.12 Mo 0.12 Sn 0.12 The preparation method of the S2 / C composite material comprises the following steps:
[0071] Weigh 0.107 g of carbon nanotubes and put them into a beaker, add 20 mL of N,N-dimethylformamide (DMF) and ultrasonicate for 15 minutes to obtain solution A, transfer solution A to an inner tank, then weigh 0.827 g of FeCl2·4H2O, 1.026 g of sublimated sulfur, 0.276 g of ZnSO47H2O, 0.162 g of MnSO4·H2O, 0.188 g of (NH4)2MoO4 and 0.182 g of SnCl2, mix and put them into the inner tank, finally add 40 mL of ethylene glycol and place it on a magnetic stirrer and stir until it is completely dissolved, stir magnetically at room temperature for 2 hours, then transfer it to a high-pressure reactor, place it in a forced air drying oven and react at 180°C for 12 hours, open the reactor after it cools to room temperature to obtain a black precipitate. The obtained precipitate was washed three times with deionized water and anhydrous ethanol respectively, and placed in a forced air drying oven at 80°C until completely dried. The dried sample needed to be further ground to obtain the target product Fe 0.52 Zn 0.12 Mn 0.12 Mo 0.12 Sn 0.12 S2 / C.
[0072] In order to further illustrate the technical effect of the present invention, the present invention is also provided with a comparative example, as follows:
[0073] Comparative Example 1
[0074] FeS2 / C material was prepared by solvothermal method: 1.590g FeCl2·4H2O and 1.282g sublimed sulfur were weighed and mixed into the inner tank, and finally 40mL ethylene glycol and 20mL N,N-dimethylformamide were added and placed on a magnetic stirrer and stirred until completely dissolved. After magnetic stirring for 2 hours at room temperature, it was transferred to a high-pressure reactor and placed in a blast drying oven to react at 180°C for 12h. After the reactor was cooled to room temperature, it was opened to obtain a black precipitate. The obtained precipitate was washed three times with deionized water and anhydrous ethanol respectively, and placed in a blast drying oven at 80°C until completely dried. The dried sample needs to be further ground to obtain the target product FeS2 / CNT.
[0075] The target products prepared in the above-mentioned Examples 1 to 11 of the present invention and Comparative Example 1 were respectively prepared into positive electrode sheet materials, and the high entropy alloy type FeS2 / C composite material (or FeS2 / CNT) was mixed with acetylene black and binder PVDF in a mass ratio of 8:1:1 and ground for 10 minutes, and 0.5 mL of nitrogen-methylpyrrolidone was added dropwise to obtain a slurry. The slurry was coated on a 15 μm copper foil and dried at 60°C for 12 hours to obtain an entropy alloy type FeS2 / C positive electrode sheet, and its performance was respectively tested. Since the effects of Examples 1 to 11 are similar, only Example 2 is taken as an example to illustrate the effects, and the results are as follows Figures 1 to 5 shown.
[0076] Figure 1 The Fe prepared in Example 2 of the present invention 0.8 Co 0.05 Cu 0.05 Ni 0.05 Mo 0.05 XRD pattern of S2 / C; Figure 1 It can be seen that the prepared sample is a single phase, and its space group is Pa-3 (205). The diffraction peaks at 2θ of 28.5°, 33.1°, 37.2°, 40.7°, 47.5°, 56.3° and 64.3° correspond to the (111), (200), (210), (211), (220), (311) and (321) diffraction crystal planes of FeS2 crystal with space group Pa-3 (205), respectively, indicating that the prepared sample is FeS2 with cubic structure.
[0077] Figure 2 The Fe prepared in Example 2 of the present invention 0.8 Co 0.05 Cu 0.05 Ni 0.05 Mo 0.05 Elemental distribution diagram of S2 / C; Figure 2 It can be seen that Fe 0.8 Co 0.05 Cu 0.05 Ni 0.05 Mo 0.05 The C, S, Fe, Co, Cu, Ni, Mo, and S elements are evenly distributed on the S2 particles, and all the constituent elements have a good overlap.
[0078] Figure 3 The Fe prepared in Example 2 of the present invention 0.8 Co 0.05 Cu 0.05 Ni 0.05 Mo 0.05 Transmission electron microscopy image of S2 / C; Figure 3 It can be seen that: Figure 3 (af) is FeS2 / CNTs and Fe 0.8 Co 0.05 Cu 0.05 Ni 0.05 Mo 0.05 HRTEM image of S2 / C sample. It can be seen from the figure that CNTs are evenly distributed and CNTs are well combined with FeS2 particles. The prepared powders all present micron-sized agglomerated particles. Compared with FeS2 / CNTs, Fe 0.8 Co 0.05 Cu 0.05 Ni 0.05 Mo0.05 The particle size of S2 / C material is reduced and the agglomeration is weakened. Figure 3 (c, f) HR-TEM clearly shows the FeS2 / CNTs and Fe 0.8 Co 0.05 Cu 0.05 Ni 0.05 Mo 0.05 Lattice fringes of S2 / C. Figure 3 - HR-TEM of (c) shows the (023) crystal plane of FeS2 / CNTs, corresponding to a lattice spacing of 0.333 nm. Figure 3 (f) HR-TEM shows Fe 0.8 Co 0.05 Cu 0.05 Ni 0.05 Mo 0.05 The (321) crystal plane of S2 / C has a corresponding lattice spacing of 0.345 nm. From the FFT image, it can be seen that the entropy stabilized Fe 0.8 Co 0.05 Cu 0.05 Ni 0.05 Mo 0.05 S2 / C materials are single-phase compounds rather than multi-phase mixtures.
[0079] Figure 4 The Fe prepared in Example 2 of the present invention 0.8 Co 0.05 Cu 0.05 Ni 0.05 Mo 0.05 S2 / C rate performance diagram; Figure 4 It can be seen from the figure that the medium entropy strategy greatly improves the rate performance of the prepared samples, especially for Fe 0.8 Co 0.05 Cu 0.05 Ni 0.05 Mo 0.05 S2 / C, at current densities of 500, 1000, 2000 and 5000 mA g -1 Under, 661.4, 637.2, 615.0 and 588.4 mA hg were provided respectively -1 When the current density returns to 500mA g -1 , its discharge specific capacity can still recover to its initial value.
[0080] Figure 5 The Fe prepared in Example 2 of the present invention 0.8 Co 0.05 Cu 0.05 Ni 0.05 Mo 0.05S2 / C at 500mA g -1 The charge and discharge cycle diagram under current density; Figure 5 It can be seen that Fe 0.8 Co 0.05 Cu 0.05 Ni 0.05 Mo 0.05 The initial discharge capacity of S2 / C is 705.9 mA h g -1 , the discharge capacity after 500 cycles is 576.8 mA hg -1 , the capacity retention rate is 81.7%.
[0081] In summary, the present invention improves the synthesis steps and equipment of the solvent thermal reaction, and uses a magnetic stirrer to stir until completely dissolved, thereby ensuring that the system is uniform during the reaction process, and the synthesized FeS2 / C material has uniform particle size, small particle size, and good dispersion. The present invention greatly improves the utilization rate of the reactants, shortens the reaction time, improves the yield, and has the advantages of simple operation, low requirements for reaction equipment, mild conditions, and mass production. A high-entropy alloy type FeS2@C composite material with excellent performance was prepared by a simple and efficient preparation method.
[0082] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a high entropy alloy type FeS2 / C composite material, characterized in that: The following steps are involved: A soluble iron source, three or four metal soluble salts, and sublimated sulfur are added to a carbon material dispersion, and then an ethylene glycol solution is added to dissolve, and a hydrothermal reaction is carried out at 180-200°C to load the carbon material on FeS2, and at the same time, a composite material with an entropy value ≥1R is obtained, that is, a high entropy alloy type FeS2 / C composite material is obtained.
2. The preparation method according to claim 1, characterized in that: The molar ratio of the soluble iron source, the soluble metal salt and the sublimated sulfur is 1:0.17 to 4:
5.
3. The preparation method according to claim 1, characterized in that: Based on the mass of the high entropy alloy FeS2 / C composite material, the mass proportion of the carbon material is 10% to 20%.
4. The preparation method according to claim 1, characterized in that: The hydrothermal reaction time is 12 to 24 hours.
5. The preparation method according to claim 1, characterized in that: The three or four metal soluble salts are selected from three or four of cobalt salts, copper salts, manganese salts, nickel salts, zinc salts, molybdenum salts, tin salts and niobium salts.
6. The preparation method according to claim 1, characterized in that: The carbon material is carbon nanotube, biomatrix carbon, graphene oxide or N, S double-doped carbon.
7. The preparation method according to claim 1, characterized in that: The iron source is FeCl2·4H2O, Fe(NO3)3, Fe(OH)(CH3COO)2 or FeSO4.
8. A high entropy alloy type FeS2 / C composite material prepared by the preparation method according to any one of claims 1 to 8.
9. Use of the high entropy alloy type FeS2 / C composite material according to claim 8 in the preparation of positive electrode materials.
Citation Information
Patent Citations
High-entropy alloy loaded graphene oxide composite material and application thereof
CN117894937A
Preparation method and application of ion-electron dual-conductivity high-entropy metal sulfide
CN118335987A
Lithium ion battery positive plate, preparation method thereof and lithium ion battery
CN118538877A
Preparation of MS2 type high-entropy metal sulfide and application of MS2 type high-entropy metal sulfide in secondary battery
CN118684280A
Method for preparing anode material of lithium-iron disulphide battery
CN1843941A